The effect of different deproteinization agents on microleakage and penetration depth of fissure sealants in permanent molars: An in vitro study - Kubra Yaman Sisman; Ezgi Baltaci; Neslihan Ozveren (Arbu Academic Publishing, 2023)
Aim: Acid etching alone is insufficient to remove organic residues from enamel, which can compromise the microretention of fissure sealants and lead to microleakage and failure. This study evaluated the impact of four different deproteinization agents on the microleakage and penetration depth of fissure sealants in human molars. Methods: A total of 170 caries-free mandibular third molars were randomly assigned to five groups (n=34 per group): (1) The Control group (acid etching only), (2) The NaOCl group (sodium hypochlorite + acid etching), (3) The Papacarie Duo group, (4) The Brix 3000 group (both papain enzyme + acid etching), and (5) The Bromelain group (10% bromelain + acid etching). Fissure sealants were applied after etching and deproteinization. Microleakage and penetration depth were evaluated after an aging process involving 1000 thermal cycles between 5-55ºC, using a dye penetration method under a stereomicroscope. Results: Within the groups, the Brix 3000 group demonstrated the most favorable microleakage scores, while the Papacarie Duo group exhibited the least favorable scores. Specifically, a microleakage score of 0 was observed in 50%, 32.4%, 23.5%, 20.6%, and 17.6% of the teeth in the Brix 3000, NaOCl, Bromelain, Control, and Papacarie Duo groups, respectively. Furthermore, a penetration depth score of 3 was observed in 29.4%, 29.4%, 26.5%, 11.8%, and 8.8% of the teeth in the Brix, Papacarie Duo, Control, Bromelain, and NaOCl groups, respectively. Conclusions: Deproteinization with Brix 3000 gel prior to acid etching in fissure sealant applications resulted in lower microleakage and greater penetration depth compared to other deproteinization agents and acid-etching alone. Deproteinization agents can be a promising way to yield favorable results.